Effects of CuCl𝟐 on the Lyotropic Liquid Crystalline Behavior in Nonaqueous and Aqueous Medium - Ravi K. Shukla; K. K. Raina (Advances in Condensed Matter Physics)
Effects of varying doping concentrations (𝑥) of CuCl𝟐 on the aggregation behaviour of cationic surfactant in nonaqueous and aqueous medium have been investigated. Mixed and pure lyotropic liquid crystalline LLC phases appeared in nonaqueous and aqueous ternary mixtures due to the fast quenching process and then characterized through polarizing optical microscopy and X-ray diffraction technique. The material parameters corresponding to these ternary nonaqueous and aqueous mixtures were evaluated to understand the mechanisms of deriving forces responsible for the modification of mesophases in the presence of metal salt.